Atypical thymoma in a horse: Diagnostic approach and application of an alternative histological classification system. (26th November 2020) - Pudert, T.; Weyrich, A.; Geburek, F.; Herden, C.; Röcken, M.
Summary: Thymoma is a rare condition in horses. This case of a 24‐year‐old Warmblood gelding that was presented with oedema and signs of vascular congestion of the left forelimb caused by a thoracic mass is described. The diagnostic work‐up included blood chemistry, cytology of pleural effusion, ultrasonography, radiography and the visualisation and collection of a tissue sample by thoracoscopy. Finally, post‐mortem findings and histopathology revealed thymic epithelial neoplasia with histomorphologic features previously unreported in horses. The unique mixture of spindle‐shaped and epithelioid tumour cells in combination with clear features of malignancy suggested the application of the Moran and Suster histological classification system for thymomas in humans (Moran and Suster, 2008, Curr. Treat. Options Oncol ., 9, 288), which has not been reported in an equine case before and fits well to the present case.